2022
DOI: 10.3390/ijms232314586
|View full text |Cite
|
Sign up to set email alerts
|

19S Proteasome Subunits as Oncogenes and Prognostic Biomarkers in FLT3-Mutated Acute Myeloid Leukemia (AML)

Abstract: 26S proteasome non-ATPase subunits 1 (PSMD1) and 3 (PSMD3) were recently identified as prognostic biomarkers and potential therapeutic targets in chronic myeloid leukemia (CML) and multiple solid tumors. In the present study, we analyzed the expression of 19S proteasome subunits in acute myeloid leukemia (AML) patients with mutations in the FMS-like tyrosine kinase 3 (FLT3) gene and assessed their impact on overall survival (OS). High levels of PSMD3 but not PSMD1 expression correlated with a worse OS in FLT3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…For the 20S proteasome, PSMA4 , PSMA5 , PSMA7 , and all seven PSMB subunits are downregulated in AML versus normal controls ( Supplementary Figure S1 ). However, similar to our observations for PSMD3 ( 25 ), patients with higher expression levels tended to have worse outcomes ( Supplementary Figures S2, S3 ).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…For the 20S proteasome, PSMA4 , PSMA5 , PSMA7 , and all seven PSMB subunits are downregulated in AML versus normal controls ( Supplementary Figure S1 ). However, similar to our observations for PSMD3 ( 25 ), patients with higher expression levels tended to have worse outcomes ( Supplementary Figures S2, S3 ).…”
Section: Resultssupporting
confidence: 87%
“…Work from our lab and others had documented increased expression of several 19S proteasome subunits in multiple cancer types compared with normal tissue ( 24 , 49 , 51 , 57–60 ). Our previous work in AML studying the non-ATPase subunits of the 19S proteasome revealed that PSMD2 , PSMD3 , PSMD7 , and PSMD9 mRNA expression levels were reduced in AML versus normal progenitors, but that high levels of expression correlated with worse overall survival in AML patients ( 25 ). In fact, the downregulation of proteasome subunits is a universal feature of AML compared with normal mononuclear cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the PSM family genes were a cluster, while the MCM family genes were a cluster. Moreover, both PSM and MCM family genes were associated with tumor progression [ 28 , 29 ]. Then, these genes were simplified by lasso regression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PSMD3 exerts an oncogenic effect on chronic myeloid leukemia (CML) by stabilizing of nuclear factor-kappa B [16], therefore, PSMD3 is considered as a potential target for anti-cancer therapeutics in CML [17]. High degrees of PSMD3 are related to a worse overall survival (OS) in FLT3 mutated AML, indicating that PSMD3 may act as a prognostic biomarker in AML [18]. Moreover, the expression of PSMD3 was significantly higher in breast cancer tissue compared to normal tissues.…”
Section: Introductionmentioning
confidence: 99%